AN APPLICATION FOR PROMOTING IN UMKM TRAINING - Samantha R; Rizka Maharani (Yayasan Putra Adi Dharma, 2023)
This study focuses on the development and evaluation of an application designed for promoting Micro, Small, and Medium Enterprises (UMKM) training initiatives. The application aims to enhance the visibility and accessibility of UMKM training programs, providing a platform for information dissemination and engagement. The research outlines the creation and features of this application, emphasizing its potential to reach a wider UMKM audience. Furthermore, the study evaluates the effectiveness of the application in promoting UMKM training, with a focus on user engagement, reach, and impact. Preliminary results indicate that the application has positively influenced the promotion of UMKM training, facilitating broader participation and improved awareness. This research contributes to the discussion on technology-driven approaches to support UMKM growth and capacity-building.